CONCEPTUALIZING TOURISM RELATIONSHIP MANAGEMENT (TRM) FRAMEWORK AND ASSESSING ITS IMPACT ON TOURISM SERVICE QUALITY, TOURIST SATISFACTION AND DESTINATION LOYALTY - Kumar Baksi, Arup; Bhusan Parida, Bivraj (ITB Journal Publisher, LPPM ITB, 2014)
This study attempts to develop a tourist relationship management (TRM) framework by assimilating assorted dimensions. The basic foundation of the TRM framework will be rested on customer relationship management (CRM) model with justified addition of dimensions compatible to tourism dynamics. Further to this the study examines the intervening effects of modified relationship dimensions on service quality perception-tourist satisfaction-destination loyalty link. The study confirmed convergence of dimensions to justify TRM framework with adequate internal reliability and validity of the scale and further revealed that perceived tourist service quality; tourist satisfaction and destination loyalty can be colinked under the intervening effects of TRM dimensional performance. The default model also holds good to lend support to the theoretical findings.